A System Engineering Approach to Disaster Resilience : Select Proceedings of VCDRR 2021 - Ghosh, Chandan; Kolathayar, Sreevalsa (Lecture Notes in Civil Engineering, 2022)
This book presents the select proceedings of the Virtual Conference on Disaster Risk Reduction (VCDRR 2021). It emphasizes on the role of civil engineering for a disaster resilient society. Various topics covered in this book are risk assessment, prevention, mitigation, preparedness and response, early warning system, hazard mapping, engineering innovations for hazard mitigation, and safe design of structures. This book is a comprehensive volume on disaster risk reduction (DRR) and its management for a sustainable built environment. This book will be useful for the students, researchers, policy makers and professionals working in the area of civil engineering, especially disaster management.